KOMITMEN POLITIK PENETAPAN UPAH MINIMUM DI MASA PEMERINTAHAN BUPATI KABUPATEN KARAWANG PERIODE 2016-2021 - Didi Suheri (Jurnal Humaniora & Sosial Sains, 2025)
The increase in minimum wages in Karawang Regency which occurred every year during the reign of Regent Cellica Nurachadiana was a form of political commitment with the Labor Union in the 2015 Pilkada. Relationships and conflicts between the Regent and the Labor Union tended to slope because the Regent was more accommodating to The interests of workers are also strengthened by the presence of political commitment. While the relationship between the Regent and Apindo tends to be poor, this is because the Regent is not accommodating to the interests of entrepreneurs, this is evidenced in the determination of UMSK 2019 which has administrative defects. In the process, the Regent plays a dominant role in determining wage increase recommendations and is likely to abuse power for practical political interests.